Inter-lingual Re-instantiation in the Process of Police Blotter Writing - Servano, Ersweetcel (Archīum Ateneo, 2021)
This dissertation is concerned with investigating whether key meanings were altered in the process of writing police blotters in English. Police blotter writing has long been one of the important activities in police stations as it is the means of recording everything that is reported to the police, particularly alleged crime incidents before investigations are conducted. This practice involves communication switches —from oral-vernacular to written-English. In writing police blotters, an assigned police officer interviews the reporting person about the details of the crime incident. After the interview, the police officer then writes the reporting person’s account of the crime event. Written texts or police blotters are then used as the basis for investigations, as attachments to court cases, and as sources for news reports. This study argues that the process of police blotter writing might affect the accuracy of the blotter. In uncovering whether the process of police blotter writing has an effect on the accuracy of the blotter, this project examines the transfer of meanings from oral- vernacular to written-English. In particular, it examines what meanings are written in relation to what meanings are said in the interviews. This study is carried out through Systemic Functional Linguistics (SFL), a theory which asserts that language construes three kinds of meanings: ideational (meanings of experience), interpersonal (meanings which enact relationships), and textual (meanings which organize texts). These meanings may be changed as they are transferred from oral-vernacular to written-English. v As a study that is situated within the research areas of language and law and Language for Specific Purposes (LSP), this is a dissertation that presents how language is embroiled in the workings of the law. It is research that argues for the importance of addressing language issues to determine what language behaviors best serve the interests of justice.